Experimental and numerical study of chip formation in orthogonal cutting of Ti-5553 alloy: the influence of cryogenic, MQL, and high pressure coolant supply - KAYNAK, YUSUF (SPRINGER LONDON LTD, 2018)
This study presents investigation of chip formation process of Ti-5553 alloy that is a next generation near beta titanium alloy and has potential to be replaced with commonly used Ti-6Al-4V due to its superior properties such as high corrosion and fatigue resistance. Experimental part of this study includes orthogonal cutting process of Ti-5553 alloy under dry, cryogenic, minimum quantity lubrication (MQL) and high pressure coolant (HPC) conditions. Various cutting speeds were taken into account to observe chip-tool contact length, forces, temperature, chip morphology resulting from various machining conditions. Experimental study demonstrates that HPC and cryogenic help to improve chip formation process of this alloy. By implementing Johnson-Cook model, orthogonal cutting process of this alloy in dry and cryogenic conditions is simulated utilizing Deform 2D commercial software. Predicted force, temperature, and chip morphology show good agreement with experimentally measured data.
Keywords: Ti-5553 alloy; Orthogonal cutting; Cooling/lubrication; Cutting forces; Finite element method; TITANIUM-ALLOYS; MACHINABILITY; TI-6AL-4V; MICROSTRUCTURE; BEHAVIOR; SPEED; TOOL; DRY